Strategies of Art - Vijayachandran, Jayadev (2010)
“Strategies of art” is an attempt to understand the business aspect of painting and strategies one can develop to attain leverage in the industry. The role played by the stakeholders of the industry is explored and how they influence the activities of the artist is seen. Various channels of sale are explored and various tactics which can be employed to stay organised as an artist is investigated. Methods of research are through qualitative research, and Action research. Through these methodology essential aspects required for an artist and the essential aspects of a painting are investigated. Hopefully this research would give a direction to anyone who is trying to make an entry into the art industry.